AYAHUASCA: THE PRODUCTION PROCESS IN MODERN CONTEXTS - Peixoto, Renato Lemes (Seven Editora, 2026)
This study investigates the history, expansion, and production process of Ayahuasca, a sacred beverage with indigenous roots in the Amazon. Using a literature review approach, the work analyzes the influence of key figures and the foundation of religious traditions such as Santo Daime and União do Vegetal. The main focus is on detailing the Ayahuasca production process, which involves the decoction of the Banisteriopsis caapi vine and Psychotria viridis leaves. The process includes ritualistic steps of collection, preparation, and repeated boiling to concentrate the beverage’s active principles. Furthermore, it examines the creation of urban centers such as Morada dos Mestres and CEU Tenda do Xamãs, which adapt these traditional practices to modern contexts. The results indicate that Ayahuasca has significant social and spiritual relevance, promoting emotional and mental well-being, but also faces legal and ethical challenges. It is concluded that Ayahuasca not only preserves ancestral traditions, but also adapts to contemporary needs, offering an accessible spiritual and therapeutic path. DOI: https://doi.org/10.56238/sevened2026.001-017